2011
DOI: 10.1002/app.34977
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and adsorption properties, toward some heavy metal ions, of a new polystyrene‐based terpyridine polymer

Abstract: A novel polymeric ligand having 2,2 0 :6 0 ,2 00 -terpyridine as pendant group was prepared through a Williamson type etherification approach for the reaction between 4 0 -hydroxy-2,2 0 : 6 0 ,2 00 -terpyridine and the commercially available 4-chloromethyl polystyrene. The chelating properties of the new polymer toward the divalent metal ions (Cu 2þ , Zn 2þ , Ni 2þ , and Pb 2þ ) in aqueous solutions was studied by a batch equilibration technique as a function of contact time, pH, mass of resin, and concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Synthesis of N 3 P 3 -(OC 6 H 4 -p-CH 2 OH) 6 (1) N 3 P 3 -(OC 6 H 4 -p-CH 2 OH) 6 was synthesized using the method reported in the literature. H 3 PO 4 (85%) was employed as the external reference for 31 P NMR measurements.…”
Section: And Zhongmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of N 3 P 3 -(OC 6 H 4 -p-CH 2 OH) 6 (1) N 3 P 3 -(OC 6 H 4 -p-CH 2 OH) 6 was synthesized using the method reported in the literature. H 3 PO 4 (85%) was employed as the external reference for 31 P NMR measurements.…”
Section: And Zhongmentioning
confidence: 99%
“…Tin(II) 2-ethylhexanoate (Sn(Oct) 2 ) (0.0487 g, 0.120 mmol) and N 3 P 3 -(OC 6 H 4 -p-CH 2 OH) 6 (1) (0.1 g, 0.114 mmol) was added to a fire dried polymerization tube. Then, e-CL (2.743 g, 24.035 mmol) was added and the mixture was stirred under argon atmosphere until a clear solution was obtained.…”
Section: And Zhongmentioning
confidence: 99%
“…Terpy motifs have been anchored onto a large number of solid supports resulting in functional materials with enhanced stability and excellent light absorption properties [18,[23][24][25][26][27][28][29]. Nishihara et al have achieved long range electron transport for molecular electric wires by assembling bis(terpyridine) metal complexes on gold surfaces.…”
Section: Introductionmentioning
confidence: 98%
“…They have resulted in the removal efficiency (%R) for Pb 2+ , Cu 2+ , Zn 2+ , and Cd 2+ were 90.8%, 89.6%, 84.5%, and 82%, respectively at pH 6. Moreover, Saadeh et al . synthesized a new PS‐based terpyridine polymer for the adsorption of Ni 2+ , Cu 2+ , Pb 2+ , and Zn 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…They have resulted in the removal efficiency (%R) for Pb 21 , Cu 21 , Zn 21 , and Cd 21 were 90.8%, 89.6%, 84.5%, and 82%, respectively at pH 6. Moreover, Saadeh et al 26 synthesized a new PS-based terpyridine polymer for the adsorption of Ni 21 , Cu 21 , Pb 21 , and Zn 21 ions. Their study showed that the maximum equilibrium capacity of the ions in the order mentioned above were about of 10, 75, 80, and 40 mg g 21 at pH 7 during 25 min, respectively.…”
Section: Introductionmentioning
confidence: 99%